2000
DOI: 10.1177/0146167200266002
|View full text |Cite
|
Sign up to set email alerts
|

Daily Well-Being: The Role of Autonomy, Competence, and Relatedness

Abstract: Emotional well-being is most typically studied in trait or trait-like terms, yet a growing literature indicates that daily (within-person) fluctuations in emotional well-being may be equally important. The present research explored the hypothesis that daily variations may be understood in terms of the degree to which three basic needs—autonomy, competence, and relatedness—are satisfied in daily activity. Hierarchical linear models were used to examine this hypothesis across 2 weeks of daily activity and well-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

80
1,065
8
71

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 1,602 publications
(1,273 citation statements)
references
References 61 publications
80
1,065
8
71
Order By: Relevance
“…As Reis et al (2000) discussed, trait (between-person) and state (within-person) effects are both conceptually and statistically independent. A trait effect relates stable individual differences to average levels of an outcome across days.…”
Section: Study 4 Mindfulness As a Predictor Of Day-to-day Self-regulmentioning
confidence: 93%
See 1 more Smart Citation
“…As Reis et al (2000) discussed, trait (between-person) and state (within-person) effects are both conceptually and statistically independent. A trait effect relates stable individual differences to average levels of an outcome across days.…”
Section: Study 4 Mindfulness As a Predictor Of Day-to-day Self-regulmentioning
confidence: 93%
“…Recent research has shown substantial variability across time in several phenomena that clearly qualify as traits, including Big Five dispositions (Sheldon, Ryan, Rawsthorne, & Ilardi, 1997), interpersonal behavior (Brown & Moskowitz, 1998), and attachment styles (LaGuardia, Ryan, Couchman, & Deci, 2000), among others. Further, both emotional states and autonomous behavior are known to vary over time both within and between persons (Reis, Sheldon, Gable, Roscoe, & Ryan, 2000;Sheldon, Ryan, & Reis, 1996). Thus, a second major purpose of this study was to assess the degree of within-person variability in mindfulness and relate it to withinperson variability in autonomy and emotional well-being.…”
Section: Study 4 Mindfulness As a Predictor Of Day-to-day Self-regulmentioning
confidence: 99%
“…Presumably, all humans have the same basic emotional systems, and arguably any person feeling much positive mood and little negative mood is thriving. Reis et al (2000), Sheldon and Bettencourt (2000), Sheldon and Elliot (1999), and Sheldon et al (1996) all used such affect-based indicators of thriving in their more limited studies of psychological needs. However, the current study moves considerably beyond these past studies, not only by sampling satisfying experiences directly but also by examining a large set of needs derived from a wide assortment of theories, not just the three needs derived from Deci and Ryan's theory.…”
Section: Evaluating the Relative Importance Of Candidate Needsmentioning
confidence: 99%
“…On the basis of our own past findings (Reis et al, 2000, Sheldon & Elliot, 1999 and self-determination theory (Deci & Ryan, 1985), we expected that autonomy, competence, and relatedness would all emerge as important needs (Deci & Ryan, in press). That is, they should have among the highest mean scores in peoples' ratings of satisfying events, and they should all be significantly and uniquely associated with event-related affect.…”
Section: Overview Of Studies and Hypothesesmentioning
confidence: 99%
“…For example, we might expect that controlling speakers would be perceived to be more pressuring, and as a result participants would feel pressured. We furthermore tested whether prosody could also shape well-being, given autonomy-supported individuals experience more happiness and self-esteem, and lower anxiety, than those who are being controlled (e.g., O'Rourke et al, 2012;Reis et al, & Ryan, 2000;Vansteenkiste & Ryan, 2013). We expected that listening to autonomy-supportive prosody would improve well-being.…”
Section: Studymentioning
confidence: 99%